120k views
3 votes
If f(x) = x4 − x3 + x2 and g(x) = −x2, where x ≠ 0, what is (f ⁄g)(x)

2 Answers

4 votes

Answer:


-x^2+x-1

Explanation:

Given functions are,


f(x) = x^4 - x^3 + x^2


g(x) = -x^2

Since,


((f)/(g))(x)=(f(x))/(g(x))


=(x^4-x^3+x^2)/(-x^2)


=-(x^2(x^2-x+1))/(x^2)


=-(x^2-x+1)


=-x^2+x-1

Hence, the value of (f/g)(x) is
-x^2+x-1

User Jan Berktold
by
5.4k points
1 vote

f(x)=x^2-x^3+x^2=x^2(x^2-x+1)\\\\g(x)=-x^2\\\\\left((f)/(g)\right)(x)=(x^2(x^2-x+1))/(-x^2)=-x^2+x-1
User Swe
by
5.5k points